2017
DOI: 10.1111/jan.13505
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive complaints, psychosocial factors and nursing work function in nurses providing direct patient care

Abstract: Nurses experiencing subjective cognitive complaints should be encouraged to address personal and environmental factors that are associated with their cognitive status. Additionally, stress reduction in nurses should be a high priority as a potential intervention to promote optimal functioning of nurses providing direct patient care. Healthcare institutions should integrate individual and institutional strategies to reduce factors contributing to workplace stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
19
0
1
Order By: Relevance
“…We detected through path analysis that the effect of cognitive complaints on engagement was specifically mediated by concerns about "attention and immediate memory" and "inhibitory control". In this regard, Barbe et al (2018) found that perceived stress and subjective cognitive complaints were associated with lower work performance. What is more, cognitive impairments may affect work safety (Fisher, Chaffee, Tetrick, Davalos, & Potter, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We detected through path analysis that the effect of cognitive complaints on engagement was specifically mediated by concerns about "attention and immediate memory" and "inhibitory control". In this regard, Barbe et al (2018) found that perceived stress and subjective cognitive complaints were associated with lower work performance. What is more, cognitive impairments may affect work safety (Fisher, Chaffee, Tetrick, Davalos, & Potter, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Concerning cognitive complaints, studies account for an association with stress. Workers with chronic stress might suffer cognitive impairments due to hippocampus damage (Barbe, Kimble, & Rubenstein, 2018). Moreover, prolonged work-related stress has a negative impact on attention, learning, and memory domains (Eskildsen et al, 2017), as on concentration, information processing (Elfering, Grebner, & Dudan, 2011), and decision-making abilities (Ceschi, Demerouti, Sartori, & Weller, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ese results suggest that burnout is associated with deficits in the cognitive control needed to monitor and update information in working memory. Similarly, Barbe et al found a linkage between perceived stress, subjective concerns about cognitive function, and impairment of work function [42]. On the contrary, Lees and Lal did not find any association between stress and cognitive performance in a sample of middle-aged nurses with a mean age of 37 years [43].…”
Section: Resultsmentioning
confidence: 91%
“…Sestry jsou vystaveny riziku poruch spánku, nedostatku spánku, špatné kvality spánku (9,10). Špatná kvalita spánku a nedostatek spánku může u sester narušit koncentraci, paměť, pozornost, výkonnost, což může ovlivnit bezpečnost pacientů (3,11,12,13). Během nočních směn plní sestry různé úkoly spojené s péčí o pacienty, jako například podávání léků, aplikace injekcí, sledování pacientů a vedení záznamů, psaní denních zpráv a další administrativní úkony.…”
Section: úVodunclassified